(untitled) (Bangladesh Journal of Pharmacology, 2015)
Prostate cancer is the major cause of cancer-related deaths worldwide in men. There are new treatment methods and drugs are being developed with promising results in two of the prostate cancer cell lines (PPC-1 and TSU-Pr1). These two cells were treated with 20 uM of axitinib combined with dasatinib for 6-72 hours. The cell viability assessed by the cytotoxicity assay. Various regulatory genes such as c-KIT, cell cycle and apoptosis and angiogenic factors were also studied. The enzyme activity of apoptosis effector caspase-3 was colorimetrically determined. Axitinib and dasatinib combination lowered the survival rate of PPC-1 cells but enhanced the survival rate of TSU-Pr1 cells. The protein expression levels in apoptosis and angiogenesis factors were also found to be in contrast between the two cell lines. PPC-1 and TSU-Pr1 cells displayed a different response to axitinib with dasatinib, which explains different expression levels of regulators of cell-cycle, apoptosis and angiogenesis.